Productivity of European Union agriculture in 2009-2018. Measurement and analysis using the aggregated productivity indexes - Rusielik, Robert (Produktywność rolnictwa Unii Europejskiej w latach 2009-2018. Pomiar i analiza z wykorzystaniem zagregowanych indeksów produktywności, 2020)
The study measured the Total Factor Productivity (TFP) of European Union (EU) agriculture in 2009-2018. Aggregated Färe-Primont productivity indexes were used for this purpose. The indexes are relative in nature, i.e. their level is determined in relation to other countries, and thus, first of all, productivity indicators were calculated for 25 EU countries. Then, an analysis of the changes in these indicators in the analysed years was performed. Based on the analysis, countries were grouped into four specific groups distinguished by differences in the level of productivity and by the dynamics and nature of changes taking place at this level. In essence, group A are countries with the highest levels of productivity throughout the period under analysis. Group B are countries characterized by an average level of productivity. Group C are countries where the level of productivity is decreasing, while group D are countries with the lowest productivity. In the next stage of research, an attempt was made to compare the identified groups in terms of selected indicators. The aim of the research was to show the differences in the level of productivity between EU countries and to try to find factors affecting this level
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 4, s. 173-186